2022
DOI: 10.3389/fpsyt.2022.862651
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Stress and Depression in COVID-19 Survivors From an Italian Cohort of Hospitalized Patients: Results From a 1-Year Follow-Up

Abstract: BackgroundMental health-related symptoms can persist over time beyond the most common respiratory clinical features of COVID-19. A recent meta-analysis underlined that mental health sequalae may be relevant for COVID-19 survivors and reported the following prevalence rates: 20% for post-traumatic stress disorder, 22% for anxiety, 36% for psychological distress, and 21% for depression. In the context of a multi-disciplinary follow-up project, we already investigated the mid-term (4 months) psychiatric outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 52 publications
0
25
0
4
Order By: Relevance
“…Prospective follow-up questionnaire studies revealed depressive and/or anxiety symptoms in between 4% to 47% of patients, probably owing to variations in methods and case definitions. Prior prospective clinical studies without control groups investigating neuropsychiatric outcomes identified PTSD in 30% (30-120 days after COVID-19 onset) and depressive and anxiety symptoms in 30% to 33% of survivors of COVID-19 (although prevalence and not incidence). However, in survey-based studies with control groups, the burden of mental health complications among cases and controls was not significantly different, in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective follow-up questionnaire studies revealed depressive and/or anxiety symptoms in between 4% to 47% of patients, probably owing to variations in methods and case definitions. Prior prospective clinical studies without control groups investigating neuropsychiatric outcomes identified PTSD in 30% (30-120 days after COVID-19 onset) and depressive and anxiety symptoms in 30% to 33% of survivors of COVID-19 (although prevalence and not incidence). However, in survey-based studies with control groups, the burden of mental health complications among cases and controls was not significantly different, in agreement with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Of all studies on post–COVID-19 conditions published by April 2021, only 21% included control individuals and 13% had matched control individuals . Most studies reporting on increased neuropsychiatric and cognitive complications in patients with COVID-19 are based on internet or telephone surveys or EHRs and have historical or no control groups . Matched and prospectively enrolled patients hospitalized during the pandemic for non-COVID-19 illnesses are required to control for the negative societal effects of the lockdown measures on mood and cognitive function, which cannot be achieved using historical cohorts .…”
Section: Introductionmentioning
confidence: 99%
“… González-Sanguino et al (2020) , in a study of a Spanish population at the beginning of the pandemic, described that 18.70% of the population may have a possible diagnosis of depression and 21.60% have a potential diagnosis of anxiety. A recent study by Gramaglia et al (2022) , showed that female sex and depressive symptoms at 4-month follow-up were associated with depressive symptoms after 12 months ( Gramaglia et al, 2022 ). These results partially relate with those of our study, since gender is not a significant factor in our results, and age is, but they support the need for intervention in the prevention and treatment of depression to improve resilience after COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests that the mental health impact may be a cause, rather than a consequence of long COVID, at least for those patients without long term organ function impairment. It is well known that the prevalence of COVID-19 survivors showing anxiety/depressive symptoms is high ( 35 , 36 ). The pandemic impacted severely on the mental health of the general population: the effects on persons who required hospital admission, especially if they experienced traumatic events such as mechanical ventilation or familiar mourns, are conceivably more severe.…”
Section: Discussionmentioning
confidence: 99%